Echinodermata Community Structure in Seagrass Ecosystem at Sijile Beach Baluran National Park - Amero, Movhalky Argeswara Delta Cancera; Wimbaningrum, Retno; Sulistiyowati, Hari (Jurnal ILMU DASAR, 2025)
Seagrass ecosystems represent one of the most important coastal ecosystems due to their crucial ecological role in maintaining marine environmental balance.This study aims to identify and analyze the community structure of Echinodermata from the classes Ophiuroidea, Echinoidea, and Holothuroidea in the seagrass ecosystem of Sijile Beach, Baluran National Park. Sampling was conducted using a systematic transect-plot method across 10 transects and a total of 100 plots. The results revealed seven Echinodermata species, with Ophiocoma scolopendrina being the most dominant (6.15 ind/m²). The Shannon-Wiener diversity index (H') was 0.98, indicating low species diversity. This low diversity is attributed to the dominance of specific species and uneven individual distribution. Although seagrass serves as a crucial habitat supporting Echinodermata survival, environmental conditions and species-specific adaptations play key roles in shaping the community structure. These findings highlight the importance of ecological studies for the conservation and management of coastal resources.